Retrospective subjective evaluation of aesthetic outcome in secondary cleft lip deformities operated with Abbe’s flap - Kumar, Kamal M.; Murthy, Jyotsna; Narayan, Naveen (International Journal of Research in Medical Sciences, 2017)
Background:The Abbe’s flap is most commonly used to repair the full thickness defects of the lip that do not involve the commissure. The Abbe flap was first introduced to correct the secondary deformity of bilateral cleft lip. By this pedicled flap, we are able to equalize the disparity which existed between the tight upper lip and excessive lower lip. Aims to study retrospective subjective evaluation of aesthetic outcome in secondary cleft lip deformities operated with Abbe’s flap. Methods:29 patients operated during the period of January 2007 - December 2011 for correction of secondary cleft lip and nasal deformity with Abbe’s flap with or without rhinoplasty were included in our retrospective study. The secondary corrective surgeries were performed by a single surgeon. The photographs of the patients were retrospectively assessed by two plastic surgeons and one oral and maxillofacial surgeon, other than the one who performed the surgery. 29 patients operated during the period of January 2007 - December 2011 for correction of secondary cleft lip and nasal deformity with Abbe’s flap with or without rhinoplasty were included in our retrospective study. The secondary corrective surgeries were performed by a single surgeon. The photographs of the patients were retrospectively assessed by two plastic surgeons and one oral and maxillofacial surgeon, other than the one who performed the surgery. Results:Out of 29 patients with secondary cleft deformities 12 were male and 17 were female. Average follow up period was 3 years. Multiple variables of the nose and the lips were used to assess the aesthetic outcome of Abbe’s flap. Conclusion:As per the subjective retrospective analysis of our study we have come to the conclusion that Abbe’s flap is a work horse for correction of shortage of tissue for the secondary cleft lip deformities. Uniform satisfactory outcome was obtained with a more natural contour and more satisfactory proportion of both lips.